# How much the x and y value in this equation below? 3x-7=4 2x-2y=8no

neela | High School Teacher | (Level 3) Valedictorian

Posted on

To find the values of x and Y in the equations,

3x-7=4 and

2x-2y =8.

From the first equation, which has only one variable x, we can solve for x:

x-7=4. Adding 7 to both sides, we get:

3x-7+7=4+7 or 3x=11 or x = 11/3 = 3 and 2/3.

From the second equation, putting  the solutiuon, x= 11/3 , we get:

2(11/3) -2y = 8 . or

22/3-8 = 2y or

(22-24)/3 =2y or

2y = -2/3 or

y=( -2/3)/2 = -1/3

So x= 3 and 2/3

y= -1/3

malkaam | Student, Undergraduate | (Level 1) Valedictorian

Posted on

3x-7=4    ---------eq(i)

2x-2y=8  ---------eq(ii)

First find the value of x from the first equation:

3x-7=4

3x = 4 + 7

3x = 11

x = 11/3

Input the value of x in eq(ii)

2x - 2y = 8

2(11/3) - 2y = 8

22/3 - 2y = 8                          (take the LCM)

(22-6y)/3 = 8

22 - 6y = 8 * 3

22 - 6y = 24

-6y = 24 - 22

-6y = 2

y = -2/6

y = -1/3

Input the values of x and y in eq(ii)

2x - 2y = 8

2(11/3) - 2(-1/3) =8

22/3 + 2/3 = 8

24/3 = 8

8 = 8

LHS=RHS

Proved.

akande | Student, Undergraduate | eNotes Newbie

Posted on

3x-7=4

3x=4+7=11

3x=11

x=11/3 = 3.667

and

2x-2y=8

since x=11/3

2(11/3) - 2y = 8

multply boyh side by 3

2(11) - 6y = 18

22 -6y = 18

-6y = 18 -22

-6y = -4

y = -4/-6

= 4/6 = 2/3 = 0.667

krishna-agrawala | College Teacher | (Level 3) Valedictorian

Posted on

3x - 7 = 4    ...  (1)

2x - 2y = 8  ...  (2)

In equation transferring the number - 7 to the left hand side of equation we get:
3x = 4 + 7 = 11

Therefore: x = 11/3

Substituting this value of x in equation (2) we get:

2*(11/3) - 2y = 8

Therefore: -2y = 8 - 22/3 = (24 - 22)/3 = 2/3

Therefore: y = (50/3)/(-2) = -1/3.

x = 11/3,  y = -1/3.

The above solution solution is give based on equation as these are given. It appears in the first equation the second term is given as -7 instead of -y. I am giving below also a solution based on the modified equations>

3x - y = 4    ...  (1)

2x - 2y = 8  ...  (2)

Multiplying both sides of equation (1) we get:

6x - 2y = 8   ...   (3)

Subtracting equation (2) from equation (3) we get:

6x - 2x  - 2y + 2y = 8 - 8

Therefore: 4x = 0

Therefore: x = 0

Substituting this value of x in equation (1) we get

3*0 - y = 4

Therefore: -y = 4

Or: y = -4